2018
DOI: 10.1371/journal.pone.0196132
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and clinical characteristics of non-asthmatic non-smokers among adults with airflow obstruction

Abstract: Background and objectivesChronic obstructive pulmonary disease (COPD) mainly develops after long-term exposure to cigarette or biomass fuel smoke, but also occurs in non-smokers with or without a history of asthma. We investigated the proportion and clinical characteristics of non-smokers among middle-aged to elderly subjects with airflow obstruction.MethodsWe retrospectively analyzed 1,892 subjects aged 40–89 years who underwent routine preoperative spirometry at a tertiary university hospital in Japan. Airfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(39 reference statements)
2
4
1
Order By: Relevance
“…In this study, the highest number of non-smokers COPD cases in men was 55.6%, this is the same as Denguezli's findings in Tunisia that cases of non-smokers COPD were male dominated by 78.3% (Denguezli et al, 2016). Different results were obtained by Hiroto Takiguchi in Japan who stated that cases of non-smokers COPD were found in women with a 72% percentage (Takiguchi et al, 2018) and Thomsen's study in Denmark with findings of non-smoking COPD cases in women by 52%. The difference in the results of this study compared to other studies may be due to different habits in the community In Indonesia, most women live at home and rarely smoke so that exposure to cigarette smoke or other pollutants is smaller than men who are often outside the home and in the work environment which causes them to be exposed to cigarette smoke both as active and passive smokers and also exposed to pollutants in travel or because of work (Brashier & Kodgule, 2012;Ngahane et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this study, the highest number of non-smokers COPD cases in men was 55.6%, this is the same as Denguezli's findings in Tunisia that cases of non-smokers COPD were male dominated by 78.3% (Denguezli et al, 2016). Different results were obtained by Hiroto Takiguchi in Japan who stated that cases of non-smokers COPD were found in women with a 72% percentage (Takiguchi et al, 2018) and Thomsen's study in Denmark with findings of non-smoking COPD cases in women by 52%. The difference in the results of this study compared to other studies may be due to different habits in the community In Indonesia, most women live at home and rarely smoke so that exposure to cigarette smoke or other pollutants is smaller than men who are often outside the home and in the work environment which causes them to be exposed to cigarette smoke both as active and passive smokers and also exposed to pollutants in travel or because of work (Brashier & Kodgule, 2012;Ngahane et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…This data is not much different from the data from Lamprecht's study in 2011 which reported the number of non-smoking COPD cases as much as 20.5% of total COPD sufferers (Lamprecht et al, 2011) and according to Thomsen's study which reported 22%. Thomsen et al, 2013) But this data is different from the findings of Takiguchi which is 34% and the findings of denguezli are 45.1% (Denguezli et al, 2016;Takiguchi et al, 2018). The data of this study with 50 cases of COPD approached the results of a study conducted by Lamprecht with 4291 subjects conducted internationally because they were both crosssectionally conducted (Lamprecht et al, 2011).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…It also states that impaired lung function growth in early life associated with a decline in lung function in adulthood induces COPD 5. COPD has been strongly associated with smoking and is clinically characterized by symptoms like cough, sputum production, and/or dyspnea. 6,7 The therapeutic line focuses on reducing the symptoms and preventing exacerbations of the disease. Bronchodilators are the mainstay which includes β 2 -agonists and anticholinergics, either used alone or in combination with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%